PENGARUH PEER TO PEER LENDING TERHADAP KINERJA UMKM KOTA AMBON - Talakua, Beatrix Adonia; Silaya, Micrets Agustina (Jurnal Manajemen dan Profesional, 2023)
ABSTRAC Small and medium-sized enterprises are an important part of the national economy, but they currently face a number of obstacles, including difficulty accessing credit. There are still a number of obstacles to overcome, one of which is difficulty in raising capital and financing due to lack of access to financial institutions. capital and finance because they are not accessible to financial institutions. Poor access to finance in Indonesia means that some small and medium-sized enterprises still cannot access financial institutions, and difficulties in accessing finance affect the performance of businesses. medium and small. To overcome this problem, the government is implementing a financial inclusion program, with technological developments now creating collaboration between technology and finance, commonly known as fintech. One of the classifications of fintech is peer-to-peer lending. The data used were collected using a questionnaire. This study uses simple regression analysis techniques using the test tool, IBM SPSS 25.0. The results of the study indicate that financing has a significant positive effect on the performance of SMEs in Ambon City. Keywords: Peer to peer lending, Financial Performance, SMEs